2011
DOI: 10.1029/2011jd016458
|View full text |Cite
|
Sign up to set email alerts
|

Transient regional climate change: Analysis of the summer climate response in a high-resolution, century-scale ensemble experiment over the continental United States

Abstract: Integrating the potential for climate change impacts into policy and planning decisions requires quantification of the emergence of sub-regional climate changes that could occur in response to transient changes in global radiative forcing. Here we report results from a high-resolution, century-scale, ensemble simulation of climate in the United States, forced by atmospheric constituent concentrations from the Special Report on Emissions Scenarios (SRES) A1B scenario. We find that 21st century summer warming pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 98 publications
(152 reference statements)
2
43
0
Order By: Relevance
“…In some winter cases, a YC during the 21st century was only obtained in the NAO corrected data, these are marked to the right (at YC = 2100). The dashed lines indicate a shift in time ± 10 yr Our results generally agree with those of Diffenbaugh et al (2011), who, based on projections with 1 GCM and 1 RCM and for a baseline of 1970−1999, found that over much of the continental USA, regional temperature change signals appeared before 2020, with some sub-regional variation. They also com pared their results to studies using CMIP3 GCMs.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In some winter cases, a YC during the 21st century was only obtained in the NAO corrected data, these are marked to the right (at YC = 2100). The dashed lines indicate a shift in time ± 10 yr Our results generally agree with those of Diffenbaugh et al (2011), who, based on projections with 1 GCM and 1 RCM and for a baseline of 1970−1999, found that over much of the continental USA, regional temperature change signals appeared before 2020, with some sub-regional variation. They also com pared their results to studies using CMIP3 GCMs.…”
Section: Discussionsupporting
confidence: 81%
“…The noise concerns internal variability that may amplify or suppress the long-term trends and subsequently complicate early detection of emerging climate change signals (DĂ©quĂ© et al 2007, Kendon et al 2010, Diffenbaugh et al 2011, Hawkins & Sutton 2012. Giorgi & Bi (2009), Diffenbaugh et al (2011) and Hawkins & Sutton (2012) showed that in global climate model (GCM) projections, regional-scale projected changes emerge over different time periods, depending on the region. In many cases, however, definite signals, not least in temperature, are ex pected during the next 1 to 2 decades.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, our analyses of anthropogenic forcing rely on global climate models that do not resolve the topographic complexity that strongly influences California's precipitation and temperature. Further investigation using high-resolution modeling approaches that better resolve the boundary conditions and fine-scale physical processes (44)(45)(46) and/or using analyses that focus on the underlying large-scale climate dynamics of individual extreme events (8) could help to overcome the limitations of simulated precipitation and temperature in the current generation of global climate models.…”
Section: Resultsmentioning
confidence: 99%
“…Drought intensity and frequency are predicted to increase in many arid and semiarid areas, including the south central USA, over the next decade (Seager et al 2007;Diffenbaugh et al 2011). Based on tree-ring reconstructions, the 2011 Texas drought was likely the most severe single-year drought there in the past millennium.…”
Section: Discussionmentioning
confidence: 99%
“…For example, little is known about root hydraulic conductance in situ, in part because of the difficulty in accessing roots, and virtually no work has assessed in situ root hydraulic conductance during severe drought. The 2011 drought in central Texas, Oklahoma, and eastern New Mexico was the most severe 1-year drought in the region since meteorological record keeping began in 1895, and these areas are predicted to become even drier over the next 50-100 years (Seager et al 2007;Diffenbaugh et al 2011). An estimated 300 million trees died in Texas between 2011 and 2013 due to the drought (Texas Forest Service 2012).…”
Section: Introductionmentioning
confidence: 99%